Association between RASSF1A promoter methylation and prostate cancer: a systematic review and meta-analysis. - Jincheng Pan; Junxing Chen; Bo Zhang; Xu Chen; Bin Huang; Jintao Zhuang; Chengqiang Mo; Shaopeng Qiu (PLoS ONE, 2013)
Prostate cancer (PCa) remains as one of the most common cause of cancer related death among men in the US. The widely used prostate specific antigen (PSA) screening is limited by low specificity. The diagnostic value of other biomarkers such as RAS association domain family protein 1 A (RASSF1A) promoter methylation in prostate cancer and the relationship between RASSF1A methylation and pathological features or tumor stage remains to be established. Therefore, a meta-analysis of published studies was performed to understand the association between RASSF1A methylation and prostate cancer. In total, 16 studies involving 1431 cases and 565 controls were pooled with a random effect model in this investigation. The odds ratio (OR) of RASSF1A methylation in PCa case, compared to controls, was 14.73 with 95% CI = 7.58-28.61. Stratified analyses consistently showed a similar risk across different sample types and, methylation detection methods. In addition, RASSF1A methylation was associated with high Gleason score OR=2.35, 95% CI: 1.56-3.53. Furthermore, the pooled specificity for all included studies was 0.87 (95% CI: 0.72-0.94), and the pooled sensitivity was 0.76 (95% CI: 0.55-0.89). The specificity in each subgroup stratified by sample type remained above 0.84 and the sensitivity also remained above 0.60. These results suggested that RASSF1A promoter methylation would be a potential biomarker in PCa diagnosis and therapy.